P198 Chemsex and antiretroviral therapy non-adherence in HIV-positive men who have sex with men: a systematic review. (8th June 2017) - Perera, Sean; Bourne, Adam H; Thomas, Sara
Abstract : Introduction: Chemsex is associated with ART non-adherence and may therefore negatively influence HIV disease progression. However, there is no systematic examination of evidence for this association. Our objective was to summarise the extent of ART non-adherence among chemsex drug-using HIV-positive MSM worldwide and to quantify the effect that chemsex has on ART non-adherence by comparing chemsex drug-users to non-chemsex drug-users. Methods: Pubmed and Embase were searched from inception to 25.06.15. Prevalence and analytical studies were included. Bias was assessed using a risk-of-bias assessment tool. Assessment of heterogeneity was conducted using I2 and Cochran-Q Chi2 statistics. Metaanalyses were conducted using fixed or random-effects methods. Metaregression assessed for formal statistical evidence of heterogeneity. Results: 3288 published and unpublished records were screened. Prevalence of ART non-adherence among chemsex drug-users (10 studies) ranged from 6% to 81%. 7 studies provided 10 effect measures for the association between chemsex drug-use and ART non-adherence. Chemsex drug-users had 23% higher odds of being ART non-adherent compared with non-chemsex drug-users (OR 1.23, 95%CI 1.10–1.38, I2 0%, p=0.372). Studies that used less specific definitions of chemsex drug-use found weak statistical evidence for an association (OR 1.96, 95%CI 0.52–7.31, I2 78.9%, p=0.009). Meta-regression failed to provide statistical evidence of why the effect varied between studies. Discussion: In HIV-positive MSM, the prevalence of ART non-adherence among chemsex drug-users varied widely. There was evidence of an association between chemsex drug-use and ART non-adherence. Paucity of studies and substantial heterogeneity between studies limited interpretation of results. Further well-conducted studies in a variety of settings are needed.